Nonlinear regression in parameter estimation from polarographic signals - Pais, A. A. C. C. (2000)
In this work we describe a detailed treatment of polarographic data curves, including error analysis, by means of nonlinear least-squares in its standard form (or resorting to the errors in variables model). Error estimates for the related parameters are additionally verified by Monte-Carlo simulation and resampling techniques.